Urgensi Dakwah dan Perencanaannya - Abdullah, Abdullah (Tasamuh: Jurnal Studi Islam, 2020)
To achieve the objectives of da'wah, these general objectives must first be formulated into more operational and evaluated objectives. In addition, strategic planning, systematic organization, good implementation, orderly, directness, and well-managed supervision of the activities to be achieved are also needed. The administration of the indictment can run effectively and efficiently when it has been prepared and planned well in advance. With planning, the implementation of da'wah can run in a more directed and orderly manner, so that it can consider what activities should take precedence and which activities should be pursued. On this basis, the activities of da'wah can be ordered in such a way, step by step that leads to the achievement of the goals and objectives set. Planning also allows the selection of appropriate actions, in accordance with the situations and conditions that are actually faced at the time the da'wah is held.